Effect of tetracycline on the bond performance of etch-and-rinse adhesives to dentin - Rodrigo Stanislawczuk; Jully Anna da Costa; Luceli Grabicoski Polli; Alessandra Reis; Alessandro Dourado Loguercio (Sociedade Brasileira de Pesquisa Odontológica, 2011)
This study evaluated the effect of modified tetracycline on the resin-dentin bond strength (µTBS), silver nitrate uptake (SNU) and solution homogeneity (SH) of two adhesives. Dentin surfaces were treated with phosphoric acid, rinsed off and either rewetted with water (control group - CO), 2% minocycline (MI), 2% doxycyline (DO) or 2% chlorhexidine (CH). Adhesive systems (Adper Single Bond 2 and Prime Bond NT) and composite were applied and light-polymerized. Specimens were sectioned to obtain bonded sticks (0.8 mm²) to test under tension at 0.5 mm/min. For SNU, specimens were immersed in silver nitrate and analyzed by EDX-SEM. SH was qualitatively analyzed after mixing the adhesives with different solvent-based solutions containing MI, DO and CH. Lower µTBS values were observed in the DO group compared with MI and CH (p = 0.01). Lower SNU was observed for MI and CH. The lowest µTBS for both adhesives was observed for the DO group (p = 0.01). Signs of phase separation were observed for DO with both adhesives. MI or CH used as rewetting solutions after acid etching did not affect the µTBS and hybrid layer quality.